STRENGTHENING CHILD CUSTODY LAWS DUE TO DIVORCE IN BIREUEN REGENCY - Azhari Saiful Anwar; Fauzi Saleh; Khairani (PT. Antis International Publisher, 2026)
Objective: This study examines the strengthening of legal protections for child custody and maintenance following divorce in Bireuen Regency. The research aims to identify the factual outcomes of the Bireuen Syariah Court rulings, analyze obstacles to the enforcement of child maintenance, propose ideal solutions, and describe the contributions of legal reforms. Method: Employing a qualitative field research approach, data were collected through interviews, observations, and documentation. Results: Data from the Bireuen Syariah Court for the period 2021-2025 records 650 cases concerning divorce and child custody claims; however, only 25% of child maintenance orders have been effectively enforced. The findings indicate that: (1) the Bireuen Syariah Court consistently awards custody rights to mothers and maintenance obligations to fathers, yet compliance rates remain low; (2) primary challenges include legal, economic, and social factors; (3) ideal solutions involve strengthening regulations, implementing wage garnishment for child support, and enhancing mediation processes; (4) legal reforms have contributed to increased legal awareness, improved mediation practices, reinforcement of customary and Sharia law, and greater access to justice. Novelty: The study recommends stricter supervision of court order enforcement and a multidimensional approach to safeguard children's rights post-divorce.